The McGraw-Hill reader issues across the disciplines - Muller, Gilbert H. 1941- (McGraw-Hill, 2000)
This cross-curricular composition reader emphasizes writing as thinking. Organized thematically, it includes prose works spanning various ages, cultures and subjects. It encourages students to respond actively to the essays and to formulate their own critical judgements.